From dilectio to caritas: How Augustine Argues in Book I of De Doctrina Christiana that “Love” (Caritas) is the Ultimate End of Biblical Hermeneutics - LI, Hao (Journal of Research for Christianity in China (JRCC), 2025)
This article addresses the terminology of “love” in Book I of Augustine’s De Doctrina Christiana. From the perspective of biblical hermeneutics, it aims to demonstrate how Augustine, by shifting the terminology from dilectio to caritas, endows “love” with three progressive layers of meaning within the interpretation of the Bible: love as action, love as relation, and love as substance. Beginning with his treatment of the “commandment of love” in the Gospel of Matthew within the dichotomy of usus-fruitio(use-enjoy), Augustine leads dilectio, as an action, toward caritas, as a relation. He thereby establishes that the central task of biblical hermeneutics is “enhancing love”, and the connotation of dilectio in terms of action is subsumed into caritas. Ultimately, Augustine alludes to the substantial nature of caritas which integrates both action and relation. This substantiality is explicitly manifested in the proposition that “the Holy Spirit is love,” through which caritas acquires the power to fortify the authority of Scripture. Therefore, caritas becomes the ultimate end of Augustine’s biblical hermeneutics.
Keywords: dilectio, caritas, De Doctrina Christiana, biblical hermeneutics, Holy Spirit